Inovasi Masker Alami Daun Bandotan Dengan Analisis Biaya Produksi dan Kelayakan Usaha - Siti Annisa Nazwa; Nur Fitriana; Nadyya Ghaisani; Riva Lina Nurhusin (CV. ITTC INDONESIA, 2026)
The demand for skincare products using natural ingredients is increasing, as people are increasingly aware of product safety and positive environmental impacts. Bandotan leaves (Ageratum conyzoides), often considered a weed, contain bioactive compounds that can be used as a natural facial mask ingredient. This study aims to analyze production costs and evaluate the feasibility of developing a natural mask from bandotan leaves. The approach used is a quantitative descriptive method by analyzing various data such as production costs, cost of goods sold, selling prices, projected revenues, and operating profits. The feasibility assessment is based on profit calculations and the product's ability to generate profits. The results show that natural masks made from bandotan leaves have an efficient cost structure, competitive selling prices, and are capable of generating positive profits. Thus, the innovation of natural masks from bandotan leaves is worthy of development as a business that has the potential to provide economic benefits and support the productive use of weeds.